Narrowband lamellar multilayer grating with low contrast MoSi2/Si materials for the soft x-ray region. (7th March 2019) - Huang, Qiushi; Feng, Jiangtao; Li, Tongzhou; Wang, Xiangmei; Kozhevnikov, Igor V; Yang, Yang; Qi, Runze; Sokolov, Andrey; Sertsu, Mewael Giday; Schäfers, Franz; Li, Wenbin; Xie, Chun; et al.
Abstract: To develop highly efficient narrow-bandwidth multilayer optics for the soft x-ray (SXR) spectroscopy, a low optical contrast MoSi2 /Si lamellar multilayer grating (LMG) was proposed and developed. The low contrast LMG allows for a large lamel width which can potentially achieve higher resolution than the conventional LMG and simplify the fabrication. As a first demonstration, a MoSi2 /Si multilayer with a d -spacing of 5 nm and 180 bilayers was deposited. The lamellar grating structure with a period of 614 nm, lamel-to-period ratio of 0.38, and lamel height of 670 nm was fabricated in the multilayer with reactive ion etching process. The SXR measurements show a high 0th-order diffraction efficiency of 16%–33% at 876 eV–1648 eV, which reaches around 80% of the unetched multilayer reflectivity. A maximal bandwidth reduction of 2.2 times was obtained compared with the multilayer mirror, indicating an energy resolution of E /Δ E = 108 at 1183 eV. The resolution can be further improved by reducing the multilayer d -spacing and increasing the etching depth.